Isolated loop of Intestine presenting as a lateral neck lump: unusual presentation of neck teratoma (Bangladesh Journal of Otorhinolaryngology, 2011)
Dermoid cysts are benign congenital lesions usually presenting as midline neck mass. They rarely appear in the lateral neck region. There is a report of dermoid cyst along with an isolated loop of intestine presenting as lateral neck swelling in a 10-year-old boy. The intestinal loop was completely separated from the pharynx and full of muconeum was found after opening the loop. Complete excision was done. After a thorough search, we conclude that this is the first reported case of neck teratoma presenting as loop of intestine. Key words: Dermoid; Teratoma; Primitive loop of intestine. DOI: 10.3329/bjo.v16i2.6850Bangladesh J Otorhinolaryngol 2010; 16(2): 133-135